Venlafaxine Interaction with Fullerene (C20): DFT Studies - Mohammad Reza Jalali Sarvestani (Journal of Chemistry Letters)
Rapid and accurate determination of venlafaxine (VNF) as an antidepressant medicine is of great importance. Therefore, in this research, (VNF) adsorption on the surface of fullerene C20 was studied by density functional theory computations. The calculated adsorption energies showed VNF interaction with C20 is experimentally possible. The negative values of enthalpy alterations, Gibbs free energy changes and great values of thermodynamic constants indicated the adsorption process is spontaneous. The negative values of adsorption enthalpy changes revealed the interaction of VNF with fullerene is exothermic. The bandgap of fullerene after adsorption of VNF increased %296.923 from 1.950 (eV) to 7.740 (eV) indicating the electrical conductivity of fullerene experienced a very sharp alteration during the interaction process. Therefore, C20 can be used as a sensor for electrochemical detection of VNF. The influence of the temperature on the VNF interaction with fullerene was also investigated and the results showed the adsorption process is more favorable in the lower temperatures.